DC-SIGN and DC-SIGNR Bind Ebola Glycoproteins and Enhance Infection of Macrophages and Endothelial Cells - Simmons, Graham; Reeves, Jacqueline D.; Grogan, Case C.; Vandenberghe, Luk H.; Baribaud, Frédéric; Whitbeck, J.Charles; Burke, Emily; Buchmeier, Michael J.; Soilleux, Elizabeth J.; Riley, James L.; Doms, Robert W.; Bates, Paul; et al. (Virology (New York, N.Y.), 2003)
Ebola virus exhibits a broad cellular tropism in vitro. In humans and animal models, virus is found in most tissues and organs during the latter stages of infection. In contrast, a more restricted cell and tissue tropism is exhibited early in infection where macrophages, liver, lymph node, and spleen are major initial targets. This indicates that cellular factors other than the broadly expressed virus receptor(s) modulate Ebola virus tropism. Here we demonstrate that the C-type lectins DC-SIGN and DC-SIGNR avidly bind Ebola glycoproteins and greatly enhance transduction of primary cells by Ebola virus pseudotypes and infection by replication-competent Ebola virus. DC-SIGN and DC-SIGNR are expressed in several early targets for Ebola virus infection, including dendritic cells, alveolar macrophages, and sinusoidal endothelial cells in the liver and lymph node. While DC-SIGN and DC-SIGNR do not directly mediate Ebola virus entry, their pattern of expression in vivo and their ability to efficiently capture virus and to enhance infection indicate that these attachment factors can play an important role in Ebola transmission, tissue tropism, and pathogenesis.